Anatomy of Terror : From the Death of Bin Laden to the Rise of the Islamic State - Ali Soufan (London Norton, 2018)
A compelling, definitive account of how and why bin Laden's ideology keeps rising from the dead. When Osama bin Laden was killed by a U.S. Navy SEAL, many prophesied al-Qaeda's imminent demise. In reality the opposite has occurred. Why? Watching the Arab Spring from his Pakistani safe house, bin Laden had seen an historic opportunity: "The next stage will be the return of the caliphate." In the six years since bin Laden's death, al-Qaeda's affiliates metastasized, and the Islamic State, its most brutal spinoff, proclaimed itself the reborn caliphate bin Laden had foreseen. Anatomy of Terror is told through the stories of the flagbearers of today's Islamic radicalism, including a Jordanian drug dealer, an air force colonel who served Saddam Hussein, a reclusive Iraqi bookworm, and one of bin Laden's own sons. Ali Soufan, a top counterterrorism operative, lays bare the psychology and inner workings of al-Qaeda, the Islamic State, and their spawn and shows how the propagation of terrorism can be stopped.
Include Index
Keywords: Bin Laden, Osama -- Terrorism--Religious aspects--Islam -- Radicalism